STRATEGI PERPUSTAKAAN KELILING DALAM UPAYA MEWUJUDKAN BUDAYA GEMAR MEMBACA WBP - Brillian Hanenda Putra (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2020)
Abstract: in 2016, the UNESCO International Agency recorded that the reading rate of Indonesian citizens was ranked 60th with a statistical data record of 0,0001%. This means that out of 1,000 Indonesians only 1 person is diligent in reading books. It is indicated that the lack of reading facilities is one of the factors that causes the lack of interest in reading Indonesian people. The mobile library facility is a solution that can be done by the government in increasing the reading interest of the Indonesian people including the WBP within the Penitentiary. The following research uses qualitative research methods with the type of literature review research. This study aims to measure the effectiveness of mobile library services in increasing interest in reading WBP as one of the fulfillment of prison functions as a place of guidance.Key Word: mobile library, interest in reading, fostering prisoners.